Pengembangan instrumen nilai kedisiplinan mata pelajaran pendidikan jasmani dan kesehatan pada SMP Negeri 2 Gombong Kabupaten Kebumen tahun pelajaran 2014 /2015 - Diyun Arifin (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2015)
This study aims to determine: (1) how the assessment discipline of Physical and Health Education’s Lesson at State Junior High Shcool 2nd Gombong Kebumen Regency year 2014/2015 teachers do at this point, (2) how the shape of the instrument, (3) how the development of the instrument, (4) what are an indicator instrument, (5) the validity and reliability of the instrument, (6) the tendency of attitude measurement results of discipline, (7) the relationship between Physical and Health Education’s Lesson with value discipline, and (8) the difference between the student discipline men with female students. This type of research is the development of research. This research was conducted in SMP Negeri 2 Kebumen Gombong. The subjects were: A seventh-grade students of State Junior High Shcool 2nd Gombong Kebumen Regency which amounts to 32 students and teachers of State Junior High School 2nd Gombong Kebumen Regency Deal. The object of this study is discipline assessment instruments Physical and Health Education’s Lesson. Based on the results of the study concluded: (1) is now part of teacher disciplinary assessment Physical and Health Education’s Lesson at Junior High School 2 Gombong by observation alone without the use of assessment instruments, (2) The form of assessment instruments Physical and Health Education’s Lesson disciplinary subjects consisted of observation instruments the value of discipline, instruments self-assessment and peer assessment instruments, (3) development of assessment instruments disciplinary subjects between the stages Sport and Healt done, namely: literature study and field surveys, the development of assessment instruments of discipline, expert validation and revision of the product, product trials, data analysis, and the final product, (4) Indicators discipline assessment instruments, namely: (a) the right time on Physical and Health Education’s Lesson, (b) comply with the rules or school rules and regulations Physical and Health subjects, (c) do/collect duties in accordance with the time Physical and Health determined, and (d) follow the rules of good writing and speaking correctly, (5) the validity and reliability of the instrument all valid and reliable instruments, (6) the results of measurements of the attitude of discipline at State Junior High Shcool 2nd Gombong Kebumen Regency including good category, and (7) There is a difference between male students with discipline female students in class VII A State Junior High Shcool 2nd Gombong Kebumen Regency Deal.